Dual-functional 3-acetyl-2,5-dimethylthiophene additive-assisted crystallization control and trap state passivation for high- performance perovskite solar cells - Saykar, Nilesh G.; Iqbal, Muzahir; Pawar, Mahendra; Chavan, Kashinath T.; Mahapatra, Santosh K. (ACS Applied Energy Materials, 2022)
Defect-mediated charge recombination and successive degradation mainly lag the performance of perovskite solar cells (PSCs). Insufficiency or evaporation of organic cations leaves behind the undercoordinated Pb2+ ions, which act as severe charge recombination centers. Herein, theoretical and experimental insights into crystallization control and defect passivation of MAPbI3 perovskite by the dual-functional 3-acetyl-2,5-dimethylthiophene (ADT) molecule are pre-sented. Density functional theory calculations show that both functional groups of ADT possessing different interaction energies could interact with PbI2. The carbonyl group in ADT shows the dominant interaction with Pb2+ forming an intermediate product that might decrease the crystallization rate. Further, the coordinate bonding between ADT and uncoordinated Pb2+ ions in perovskite leads to defect passivation. The 0.6% ADT-modified PSCs possess an average power conversion efficiency (PCE) of 18.22 +/- 0.80% and the highest PCE of 19.03%, whereas the pristine PSCs exhibit an average PCE of 16.23 +/- 1.32% and the highest PCE of 17.47%. Furthermore, the modified PSCs maintain 80% of the initial PCE up to 650 h during storage at ambient conditions (RH = 35 +/- 5%). The present study shows that the simultaneous crystalization control and defect passivation achieved via an ADT additive engineering approach could be an efficient strategy to enhance the PCE and stability of PSCs.
Keywords: 3-acetyl-2; 5-dimethylthiophene; additive engineering; crystallization control; defect passivation; Perovskite solar cells